Use of a novel statistical technique to examine the delivery of breast cancer follow‐up care by different types of oncology providers. Issue 5 (17th March 2016) - Neuman, Heather B.; Rathouz, Paul J.; Winslow, Emily; Weiss, Jennifer M.; LoConte, Noelle K.; Lin, Chee Paul; Wurm, Mike; Smith, Maureen A.; Schrag, Deborah; Greenberg, Caprice C.
Abstract: Rationale, aims and objectives: Frequent follow‐up is recommended for the more than 3 million breast cancer survivors living in the USA. Given the multidisciplinary nature of breast cancer treatment, follow‐up may be provided by medical oncologists, radiation oncologists, surgeons and primary care providers. This creates the potential for significant redundancy as well as gaps in care. The objective was to examine patterns of breast cancer follow‐up provided by different types of oncologists and develop a statistical means of quantifying visit distribution over time. Methods: We identified stage I–III breast cancer patients who underwent breast conservation from 2000 to 2006 ( n = 12 139) within the SEER‐Medicare linked database. Provider type was defined using Medicare specialty provider codes and AMA Masterfile. The coefficient of variation (CV) for time between oncologist follow‐up visits was calculated. Ordinal logistic regression assessed factors associated with CV. Results: Substantial variation in CV was observed. Sixty‐seven per cent of patients with low CV (high visit regularity) received follow‐up from a single oncologist type, versus 8% with high CV (low visit regularity). The number of oncologist types participating in follow‐up had the greatest association with high CV (odds ratio 7.4 [6.7–8.3] and 15.4 [13.6–17.6] for two and three oncologist types). Conclusions: Using a novel means of quantifying follow‐up visit regularity, we determined that breast cancer patients with dispersed follow‐up with more than one oncologist have more disordered care. The CV could be used in electronic medical records to identify cancer survivors with more disordered.